Licorice-Yuanhua Herbal Pair Induces Ileum Injuries Through Weakening Epithelial and Mucous Barrier Functions: Saponins, Flavonoids, and Di-Terpenes All Involved - Yu, Jingao; Zhang, Dongbo; Liang, Yanni; Zhang, Zhen; Guo, Jianming; Chen, Yanyan; Yan, Yafeng; Liu, Hongbo; Lei, Liyan; Wang, Zheng; Tang, Zhishu; Tang, Yuping; et al. (Frontiers in Pharmacology, 2020)
In traditional Chinese Medicine (TCM), the licorice-yuanhua herbal pair is one of the most representative incompatible herbal pairs recorded in the “eighteen incompatible herbal pairs” theory. Previous studies of our research group have demonstrated several gut-related side-effects induced by licorice-yuanhua herbal pair. In this study, we investigated whether and why this incompatible herbal pair could induce gut tissue damages. After licorice-yuanhua treatment, mice duodenum, ileum and colon as well as serum biomarkers were examined by pathological staining, western blot and ELISA assays. The IEC-6 cells and LS174T cells were treated with licorice saponins, yuanhua flavonoids and di-terpenes, the iTRAQ-labeled proteomic technology was used to explore their synergistic effects on mucosa cells followed by verification of ZO-1 and MUC-2 protein expressions. Results found that licorice-yuanhua herbal pair induced ileum tissue injuries including epithelial integrity loss, inflammation and edema. These injuries were verified to be related with epithelial and mucous barrier weakening, such as down-regulated ileum ZO-1 and MUC-2 protein expressions. Proteomic analysis also suggested that glycyrrhizic acid and genkwanin synergistically influence tight junction pathways in LS174T cells. Furthermore, licorice saponins, yuanhua flavonoids and di-terpenes dose/structure dependently down regulate ZO-1 and MUC-2 protein expressions in mucosa cells. Our study provide different insights into the incompatibility mechanisms and material basis of licorice-yuanhua herbal pair, especially in that: besides toxic di-terpenes, licorice saponins and yuanhua flavonoids, the commonly known non-toxic compounds, can also take part in gut damages induced by licorice-yuanhua herbal pair.